Energy reserves of parasitoids depend on honeydew from non-hosts - Tena, Alejandro; Pekas, Apostolos; Wackers, Felix L.; Urbaneja, Alberto (2017)
Adult parasitoids depend on sugar-rich foods such as nectar and honeydew to meet their energy requirements and control insect pests. However, it is poorly known whether parasitoids can detect and feed on honeydew in agroecosystems, where it is the primary carbohydrate source, because this sugar source is less apparent in comparison to nectar and sometimes contains repellent compounds for parasitoids.